“PSYCHOLOGICAL PREDICTORS OF COPING STRATEGIES IN CHILDREN EXPOSED TO VIOLENCE” (Multidisciplinary Journal of Science and Technology, 2026)
This study examines the psychological predictors of coping strategies in children exposed to violence. Exposure to violence is recognized as a significant risk factor affecting children’s emotional and behavioral development. The research aims to identify key psychological variables, including anxiety, self-esteem, and perceived social support, that influence the formation of adaptive and maladaptive coping strategies. The study was conducted using a quantitative approach with a sample of school-aged children who have experienced various forms of violence. Standardized psychological assessment tools were employed to measure coping strategies and related psychological factors. Statistical analysis, including correlation and comparative methods, was used to determine the relationships between variables.The findings indicate that higher levels of perceived social support and self-esteem are associated with the use of adaptive coping strategies, while increased anxiety is linked to maladaptive coping patterns. These results highlight the importance of psychological and social resources in fostering resilience among children exposed to violence. The study contributes to the existing literature by providing empirical evidence on the role of psychological predictors in coping strategy development. The findings can be used to design effective psychological interventions and support programs for vulnerable children.